1985
DOI: 10.1113/jphysiol.1985.sp015608
|View full text |Cite
|
Sign up to set email alerts
|

Lateral filamentary spacing in chemically skinned murine muscles during contraction.

Abstract: SUMMARY1. A mouse toe muscle was chemically skinned with saponin and the 1,0 spacing of the hexagonal myofilament lattice at a sarcomere length of 2-5 Itm was measured with the X-ray-diffraction method. In the relaxed state, the 1,0 spacing was 40-8 nm.2. When the muscle was maximally activated at pCa 4 4, the spacing decreased to 38-4 nm. During contractions at lower calcium concentrations, the spacing decreased less. In rigor, the spacing decreased to almost the same extent as during maximum contraction, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
60
4

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 24 publications
13
60
4
Order By: Relevance
“…Interfilament spacing is a sensitive function of SL (11,12,19). Furthermore, significant changes in interfilament spacing have been reported to occur during activation in skeletal muscle (3,27). There may be a direct effect of interfilament spacing on myofilament Ca 2ϩ responsiveness (11,12,15,28,36).…”
Section: Discussionmentioning
confidence: 99%
“…Interfilament spacing is a sensitive function of SL (11,12,19). Furthermore, significant changes in interfilament spacing have been reported to occur during activation in skeletal muscle (3,27). There may be a direct effect of interfilament spacing on myofilament Ca 2ϩ responsiveness (11,12,15,28,36).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are qualitatively similar to those reported by Bagni et al (1995) from single frog fibres, which showed large reductions in the passive tension components following mechanical skinning. Skinning of frog muscle fibres is known to result in expansion of the filament lattice (Matsubura & Elliot, 1972;Goldman & Simmons, 1986) and, in skinned mouse muscle fibres, addition of •3% dextran to the relaxing solution is thought to restore the filament lattice spacing to intact fibre dimensions (see Matsubara, Umazume & Yagi, 1985). In a few experiments, the effects of adding 4% dextran on the tension response to a ramp stretch was examined after a preparation was skinned.…”
Section: The Effects Of Chemical Skinning (At 10°c)mentioning
confidence: 99%
“…It was shown that the radial force generated by attached cross-bridges in activated and rigor states varied as a function of filament separation (Matsubara et al 1984(Matsubara et al , 1985Brenner & Yu, 1985, 1991. At large separations, the direction of the force is toward the centre of the fibre; its magnitude decreases monotonically with decreasing d1o until it reaches zero at the equilibrium spacing.…”
Section: Introductionmentioning
confidence: 99%
“…In skinned striated muscle fibres, where the surface membrane is made permeable or removed, the spacing between the contractile filaments decreases in transition from the relaxed state to isometric contraction (Shapiro, Tawada & Podolsky, 1979;Matsubara, Umazume & Yagi, 1985;Brenner & Yu, 1985, 1991, or to the rigor state (Maughan & Godt, 1981;Matsubara, Goldman & Simmons, 1984;Brenner, Yu & Podolsky, 1984;Umazume & Kasuga, 1984), suggesting that force is generated in the radial direction. Experimental evidence supports the idea that the radial force is generated by attached cross-bridges.…”
Section: Introductionmentioning
confidence: 99%